The Effect of Inflation, Exchange Rate, and Unemployment on Financing of the Islamic Commercial Bank Sector in Indonesia - Abdullah Abdullah (Niqosiya: Journal of Economics and Business Research, 2024)
MSMEs are one of the main factors in encouraging national economic development, but the MSME sector in Islamic banking has fluctuated from year to year in Indonesia. This study aims to analyze the influence of the macro economy on financing the MSME sector in Islamic banking in Indonesia. This study uses time series data, namely monthly data on the financial statements of Islamic Commercial Banks and data on macroeconomic variables for 2018-2022 in Indonesia. The analysis method used in this research is Autoregressive Distributed Lag (ARDL). The results of this study indicate that this affects the financing of the MSME sector of Islamic Commercial Banks in the short-term inflation. In the long term, inflation affects the financing of the MSME sector of Islamic Commercial Banks. Other variables, namely exchange rates and unemployment, cannot affect the financing of the MSME sector of Islamic Commercial Banks.